Zebrafish cornea formation and homeostasis reveal a slow maturation process, similarly to terrestrial vertebrates’ corneas - Ikkala, Kaisa; Raatikainen, Sini; Koivula, Henri; Michon, Frederic (Frontiers in Physiology, 2022)
Corneal blindness is the fourth leading cause of blindness worldwide. The superficial position of cornea on the eye makes this tissue prone to environmental aggressions, which can have a strong impact on sight. While most corneal pathology studies utilize terrestrial models, the knowledge on zebrafish cornea is too scarce to comprehend its strategy for the maintenance of a clear sight in aquatic environment. In this study, we deciphered the cellular and molecular events during corneal formation and maturation in zebrafish. After describing the morphological changes taking place from 3 days post fertilization (dpf) to adulthood, we analyzed cell proliferation. We showed that label retaining cells appear around 14 to 21dpf. Our cell proliferation study, combined to the study of Pax6a and krtt1c19e expression, demonstrate a long maturation process, ending after 45dpf. This maturation ends with a solid patterning of corneal innervation. Finally, we demonstrated that corneal wounding leads to an intense dedifferentiation, leading to the recapitulation of corneal formation and maturation, via a plasticity period. Altogether, our study deciphers the maturation steps of an aquatic cornea. These findings demonstrate the conservation of corneal formation, maturation and wound healing process in aquatic and terrestrial organisms, and they will enhance the use of zebrafish as model for corneal physiology studies.